Geographies of Cubanidad : Place, Race, and Musical Performance in Contemporary Cuba - Bodenheimer, Rebecca M. (Book collections on Project MUSE., 2015)
The concept of Cubanidad has always imagined a unified hybrid nation where racial difference is nonexistent and nationality trumps all other identities. However, scholars have highlighted the gap between the claim of racial harmony and the realities of inequality. In this work, Rebecca M. Bodenheimer argues that it is not only the recognition of racial difference that threatens to divide the nation, but that popular regional sentiment further contests the hegemonic national discourse.